Role of the community pharmacist in detecting frailty and spatio-temporal disorientation among community-dwelling older people in France - Rhalimi, Mounir; Housieaux, E.; Mary, A.; Detuncq, C.; Muller, A.; Georgin, F.; Comby, F.; Wehrlé, C.; Davoust, N.; Brazier, M. (Aging Clinical and Experimental Research, 2021)
Background Many older community-dwelling subjects may be frail and/or disoriented, putting them at risk of adverse outcomes. We investigated the prevalence of frailty and spatiotemporal disorientation among patients aged > 65 years collecting regular medication at a community pharmacy. Methods Prospective, cross-sectional study of geriatric evaluation in 218 community pharmacies in France. Regular customers aged > 65 years attending the pharmacy to receive ≥ 1 prescription drug were eligible. Spatio-temporal disorientation was assessed using a 4-item screening test; subjects were considered disoriented if they had ≥ 1 incorrect answers. Frailty was evaluated using the Short Emergency Geriatric Assessment (SEGA) grid. Subjects were considered as not frail (score < 8), or frail/very frail (score of 8 or more). Results 4090 subjects were included, average age 77.5 ± 7.6 years, 60.1% females. Overall, 1025 (25%) were frail/very frail, and 384 (9.4%) were disoriented in space or time. On average, subjects were taking 5.4 ± 3.5 medications per day. Among non-frail patients, 116/3065 (3.8%) were disoriented, of whom 87 (87/116, 75%) managed their medication alone. Among frail/very frail patients, 268/1025 (26.1%) were disoriented, of whom 46 (46/268, 16.8%) managed their medication alone. The majority of patients (77.9%) collected their medication alone at the pharmacy, but significantly fewer frail patients came to collect their drugs alone ( p < 0.001). Conclusion It is feasible for community pharmacists to detect disorientation and frailty among older patients. A quarter of subjects were frail/very frail, and 3.2% were disoriented yet managing their drugs alone. Additional social support should be envisaged for these subjects.